2016
DOI: 10.1016/j.jpor.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ enhances the efficacy of autogenous bone grafts by inhibiting postoperative bone resorption in rat calvarial defects

Abstract: Local IFN-γ administration promoted bone formation in autogenous bone grafts possibly via regulating osteoclastogenesis and TNF-α expression. The data provide insights into the potential roles of IFN-γ in autogenous bone grafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Moreover, the development of new osteoinductive and osteoconductive materials and the search for the most effective endogenous stimulation in bone repair have been the goals of different studies . Bone substitutes are directly linked to their biocompatibility and ability to initiate or accelerate the repair process and, when combined with other bioinductive techniques, can provide promising results in the bone repair process and in surgical treatment . Inorganic bovine bone is a well‐known bone graft and it has been used in different areas of reconstructive surgery and ambulatory procedures that aim bone repair because it is similar to human bone.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the development of new osteoinductive and osteoconductive materials and the search for the most effective endogenous stimulation in bone repair have been the goals of different studies . Bone substitutes are directly linked to their biocompatibility and ability to initiate or accelerate the repair process and, when combined with other bioinductive techniques, can provide promising results in the bone repair process and in surgical treatment . Inorganic bovine bone is a well‐known bone graft and it has been used in different areas of reconstructive surgery and ambulatory procedures that aim bone repair because it is similar to human bone.…”
Section: Introductionmentioning
confidence: 99%
“…For example, patients with reduced alveolar bone height often undergo alveolar bone augmentation before a dental implant can be placed. Presently, autograft, allograft, xenograft, and bone grafting materials are used for alveolar bone augmentation; however, it is difficult to maintain the grafted bone height and volume for a long period after the augmentation treatment [4], even following autograft bone augmentation [5], [6], which is considered the gold-standard procedure.…”
Section: Introductionmentioning
confidence: 99%
“…We observed the levels of IFN-γ one and eight weeks after surgery and found that the level of IFN-γ was significantly increased by exercise. Exercise could recruit and activate macrophages, activate CTL, and promote B cell to produce opsonizing antibodies as an immune regulator [27,28]. Our results show that the amount of new bone tissues in running groups was significantly higher than that in negative control group, indicating that there may be a relationship between osteoinduction and immunity, which will be explored in further studies.…”
Section: Discussionmentioning
confidence: 68%